Markups, market imperfections, and trade openness: Evidence from Ghana - Kaku Attah Damoah (FIW - Research Centre International Economics, 2018)
This paper investigates the impact of Ghana's WTO accession on firm-level product and labour market imperfections. We exploit a rich dataset of firm-level information to estimate both markups and the degree of monopsony power enjoyed by manufacturing firms. Results suggest that price-cost margins declined, while the degree of monopsony power increased in the wake of WTO accession. These diverging dynamics suggests that firms compress real wages to offset loss of market power in the product market due to increased international competition. This results in an increase of the market imperfection gap, which gradually erodes the pro-competitive gains from trade. The paper contributes to the literature by identifying channels through which allocative inefficiencies and misallocation can persist even after trade liberalisation.
Keywords: F13; L11; O14; O24; 330; Markups; Market Imperfections; Trade Openness; Africa; Ghana